2023
DOI: 10.1136/bmjopen-2022-062322
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hyperbaric oxygen therapy for fibromyalgia: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate the efficacy and safety of hyperbaric oxygen therapy (HBOT) for fibromyalgia (FM).DesignA systematic review and meta-analysis.Data sourcesPubMed, EMBASE, Cochrane Library, Web of Science, VIP (China Science and Technology Journal Database), CNKI (China National Knowledge Infrastructure) and WanFang database were searched from from inception to 22 October 2022.Eligibility criteriaWe included clinical trials (randomised controlled and non-randomised controlled trials) of HBOT for FM.Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…On the other hand, even though the present work used hyperbaric oxygenation at lower pressures in comparison to other works that have demonstrated safety even with longer treatments [ [40] , [41] , [42] ], the present study describes a short treatment and 28 days of follow-up, which constitutes a possible limitation to the detection of toxicities that occur at remote times. This possibility cannot be completely ruled out.…”
Section: Limitations Of the Studymentioning
confidence: 92%
“…On the other hand, even though the present work used hyperbaric oxygenation at lower pressures in comparison to other works that have demonstrated safety even with longer treatments [ [40] , [41] , [42] ], the present study describes a short treatment and 28 days of follow-up, which constitutes a possible limitation to the detection of toxicities that occur at remote times. This possibility cannot be completely ruled out.…”
Section: Limitations Of the Studymentioning
confidence: 92%
“…The current indications of HBOT can be broadly classified into three categories: the acceleration of wound healing and enhancement of angiogenesis, enhancement of antimicrobial effects, and some medical emergencies, such as arterial gas embolism and decompression sickness [4]. Emerging research has shown the potential benefits of HBOT in neurological disorders and other syndromes associated with chronic fatigue [5,6]. Several studies have observed improved cognitive functions attributed to HBOT [7][8][9].…”
Section: Hyperbaric Oxygenation Therapy As a Potential Treatment For ...mentioning
confidence: 99%
“…The proposed mechanisms for such benefits include improved oxygenation to the ischemic tissues, reduced activation of glial cells and other inflammatory mediators causing an anti-inflammatory effect, and improved metabolic function. 71 Lastly, improved flexibility specifically after stretching exercise was reported as a mechanism for pain relief, 41 , 49 but no studies investigating the relationship between improvements in flexibility and pain were cited. It has been proposed that stretching exercise reduces the sensitivity of tender points and fear of movement associated with pain.…”
Section: Physical Mechanismsmentioning
confidence: 99%